Identifikasi Jenis Kegagalan Persalinan Normal pada Ibu Remaja - Suhartatik Suhartatik; Wa Mina La Isa; Susi Sastika Sumi; Ernawati Ernawati (Journal of Telenursing (JOTING), 2023)
This study aims to identify the incidence of failure of normal delivery in teenage mothers at the Masyita Women's and Children's Hospital in Makassar City. The method used is quantitative research with a cross-sectional approach. The results of this study showed that there were 46 cases of uterine inertia (25.0%), 70 cases of premature rupture of membranes (38.0%), 24 cases of severe preeclampsia (13.0%), 24 cases of preeclampsia placenta previa as many as 8 people (4.3%). the incidence of prolonged labor was 36 people (19.6%). The conclusion of this study is that there are several findings of failure of normal delivery in teenage mothers including inertia, premature rupture of membranes, severe preeclampsia, placenta previsa and prolonged parturition. Keywords: Adolescent Mothers, Types of Childbirth, Failure of Normal Childbirth